ANALISIS PEMBENTUKAN KARAKTER BERKEBINEKAAN GLOBAL MELALUI METODE BERCERITA UNTUK PESERTA DIDIK KELAS 4 SEKOLAH DASAR - Maghfiroh, Nurun; Umam, Nanang Khoirul (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2023)
Global diversity is one of the profiles of Pancasila students that students must learn, namely respecting diversity and not closing themselves from outside cultures. Global, diverse characters can be formed through storytelling methods. This study aims to analyse the formation of international diversity characters by telling stories to students. This study uses a qualitative method of descriptive approach to describe events that take place during data collection. Data collection techniques in this study used observation, interviews, and questionnaires, with the subject of grade 4 students of UPT SD N 12 Gresik, totalling 29 students. The results showed that the formation of global diversity characters by telling stories to students was quite good. Activities that are fun and attract students’ attention affect the appearance of international diversity character. Efforts can be made to give direction to attitudes that are felt incompatible with the meaning of global diversity.